Diversity in the fertilization envelopes of echinoderms. Issue 1 (20th January 2013) - Oulhen, Nathalie; Reich, Adrian; Wong, Julian L.; Ramos, Isabela; Wessel, Gary M.
SUMMARY Cell surface changes in an egg at fertilization are essential to begin development and for protecting the zygote. Most fertilized eggs construct a barrier around themselves by modifying their original extracellular matrix. This construction usually results from calcium‐induced exocytosis of cortical granules, the contents of which in sea urchins function to form the fertilization envelope (FE), an extracellular matrix of cortical granule contents built upon a vitelline layer scaffold. Here, we examined the molecular mechanism of this process in sea stars, a close relative of the sea urchins, and analyze the evolutionary changes that likely occurred in the functionality of this structure between these two organisms. We find that the FE of sea stars is more permeable than in sea urchins, allowing diffusion of molecules in excess of 2 megadaltons. Through a proteomic and transcriptomic approach, we find that most, but not all, of the proteins present in the sea urchin envelope are present in sea stars, including SFE9, proteoliaisin, and rendezvin. The mRNAs encoding these FE proteins accumulated most densely in early oocytes, and then beginning with vitellogenesis, these mRNAs decreased in abundance to levels nearly undetectable in eggs. Antibodies to the SFE9 protein of sea stars showed that the cortical granules in sea star also accumulated most significantly in early oocytes, but different from sea urchins, they translocated to the cortex of the oocytes well before meiotic initiation. These results suggest that the preparation for cell surface changes in sea urchins has been shifted to later in oogenesis, and perhaps reflects the meiotic differences among the species—sea star oocytes are stored in prophase of meiosis and fertilized during the meiotic divisions, as in most animals, whereas sea urchins are one of the few taxons in which eggs have completed meiosis prior to fertilization.